THE POTENTIAL OF HALAL TOURISM IN AL-AKBAR NATIONAL MOSQUE SURABAYA - Mulyatiningsih Mulyatiningsih; Sri Herianingrum (Universitas Airlangga, 2020)
The purpose of this study was to determine the potential of halal food, Muslim clothing, Islamic finance in the Al-Akbar Mosque as a tourist attraction. This research uses a qualitative approach with a case study strategy. The research method used was a case study with a descriptive qualitative approach. This study uses interviews as the primary data collection method. The scope of this research focuses on administrators, visitors, and traders at the Al-Akbar National Mosque in Surabaya. The results of the study found that the theme of food, fashion, and finance at the Al-Akbar National Mosque in Surabaya has been properly organized to make the Al-Akbar National Mosque tour as a modern Islamic tourKeywords: Halal tourism, Halal food, Muslim fashion, Islamic finance